2023
DOI: 10.1021/acs.jafc.3c02245
|View full text |Cite
|
Sign up to set email alerts
|

Gum Arabic-Stabilized Ferric Oxyhydroxide Nanoparticles for Efficient and Targeted Intestinal Delivery of Bioavailable Iron

Abstract: Nanostructured iron(III) compounds are promising food fortificants with desirable iron bioavailability and food compatibility. Here, gum arabic (GA) solubilized 252 mg of iron(III) per g at neutral pH in the form of GA-stabilized ferric oxyhydroxide nanoparticles (GA-FeONPs) with Z-average size of 142.7 ± 5.9 nm and ζ-potential of −20.50 ± 1.25 mV. Calceinfluorescence-quenching assay revealed well-absorbed iron from GA-FeONPs by polarized Caco-2 cells due to efficient macropinocytic internalization and asialog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…These findings indicate that the LVDDHFL–iron complex could potentially be taken up through receptor-mediated endocytosis. Li et al conducted a study demonstrating that gum arabic-stabilized ferric oxyhydroxide nanoparticles can be absorbed by small intestine cells via specific endocytosis mediated by the asialoglycoprotein receptor …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that the LVDDHFL–iron complex could potentially be taken up through receptor-mediated endocytosis. Li et al conducted a study demonstrating that gum arabic-stabilized ferric oxyhydroxide nanoparticles can be absorbed by small intestine cells via specific endocytosis mediated by the asialoglycoprotein receptor …”
Section: Resultsmentioning
confidence: 99%
“…In adults, iron deficiency can result in severe fatigue and various health complications in adults, while in infants, it can cause delayed physical and mental development . Although dietary iron is available from diverse animal and plant-based sources, its bioavailability is limited, which presents challenges in achieving adequate iron intake through diet.…”
Section: Introductionmentioning
confidence: 99%
“…In industry, GA is used as an emulsifier and thickening agent . In recent years, its ability to act as a biocompatible shell for nanostructures has triggered enormous interest in medical research . In nanomedicine, the use of GA to synthesize/stabilize nanoparticles synthesized by different approaches has been extensively reported. ,, The functional groups of GA (mainly carboxylate and amine) can easily interact with the surface of nanoparticles, providing both electrostatic as well as steric stability to the final nanocomposite. , Additionally, GA is capable of preventing the aggregation of nanoparticles in the presence of components of biological fluids in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, gum arabic has been used as a natural functional ingredient for the fortification of trace elements such as Fe and Zn [42], wherein these ions are chelated by the self-assembled polymer host. Similarly, Li et al [43] have shown that gum arabic facilitates the endocytic uptake of ferric oxyhydroxide nanoparticles by micropinocytosis. These authors, in an animal model (rats), also found a higher Fe bioavailability and serum Fe concentration for a gum arabic-ferric nanoparticle mixture versus ferrous sulphate.…”
Section: Gum Arabicmentioning
confidence: 86%